Developing a WebQuest-Assisted Problem-Based Learning Model to Enhance Learning Motivation and Outcomes: The Moderating Role of Self-Concept - Kania Rahma Danti Pohan; Saidun Hutasuhut; Muhammad Fitri Rahmadana (Yayasan Sembilan Pemuda Indonesia, 2027)
This study aimed to develop and evaluate a WebQuest-assisted Problem-Based Learning (PBL) model to enhance vocational high school students’ learning motivation and learning outcomes, with self-concept serving as a moderating variable. A Research and Development (R&D) approach employing the Four-D (4D) model was adopted, involving 72 tenth-grade students from SMK Sinar Husni 1, Indonesia, assigned to experimental and control groups. Feasibility was evaluated through expert validation (material, media, and instructional design), practicality via teacher and student questionnaires, and effectiveness using Multivariate Analysis of Variance (MANOVA), with the moderating effect of self-concept examined through two-way ANOVA. Validation confirmed model feasibility (material: 77.5%; media: 75.0%; instructional design: 73.33%) and high practicality (student responses: 86.68%; teacher responses: 90%). MANOVA revealed significant improvements in learning motivation and outcomes (F = 290.084; p < .001), while two-way ANOVA demonstrated a significant interaction between self-concept and the model (F = 15.671; p < .001). This study uniquely integrates WebQuest technology with PBL and examines self-concept as a moderating variable in vocational education, an underexplored combination in existing literature. The model offers a replicable instructional framework for vocational teachers to enhance student engagement and achievement through technology-supported, problem-based strategies. This research contributes empirical evidence that the WebQuest-assisted PBL model effectively enhances vocational students’ motivation and academic outcomes, with self-concept strengthening its effectiveness, providing actionable insights for curriculum developers and educators.